Electrochemical test mold
By increasing the electrode spacing and adding a large-capacity electrolyte tank in the electrochemical testing mold, eliminating the diaphragm, and setting vertically aligned electrode-electrolyte contact holes, the problems of short circuits between electrode plates and electrolyte depletion were solved, achieving high-precision and high-consistency electrochemical testing.
Patent Information
- Application Number
- CN202422594206.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2034-10-28
AI Technical Summary
In existing lithium-ion battery electrochemical testing devices, it is difficult for the electrode plates to be aligned, which can easily lead to short circuits. The separator affects the testing accuracy, and the electrolyte is easily depleted, resulting in a large discrepancy between the test results and the actual results, and insufficient accuracy and consistency.
Design an electrochemical testing mold, increase the electrode spacing, use a chamber with a diameter greater than 10 mm, eliminate the diaphragm, set vertically facing electrode-electrolyte contact holes with an area ratio of (0.8-1.3):1, use detachable connecting components to fix the electrode sheets, and ensure that the electrolyte chamber volume is greater than 5 mL.
It improves the accuracy and consistency of electrochemical testing, avoids problems such as short circuits and insufficient electrolyte, ensures sufficient electrolyte supply and efficient utilization of activation area, reduces experimental errors, and improves the accuracy and success rate of testing.
Smart Images

Figure CN223551659U_ABST
Abstract
Description
Technical Field
[0001] This utility model belongs to the field of battery technology, specifically relating to an electrochemical testing mold. Background Technology
[0002] Lithium-ion batteries, with their high energy density and long cycle life, have been increasingly widely used in recent years, thus placing higher demands on their performance. Currently, a common testing method involves sequentially stacking the casing, electrode plates, separator, electrode plates, gaskets, and spring contacts, followed by electrolyte injection / stamping. After the battery stabilizes, tests are performed on battery impedance, charge / discharge performance, cycle life, and rate performance. For example, the testing device described in utility model CN210514170U includes a separator, electrode plates, battery casing, and current collector. The tabs are either separately or integrally formed within the current collector, and the electrode plates are separated by the separator and confined within symmetrically positioned grooves on the current collector. Grooves are also created on the current collector to achieve battery sealing. While this testing device can improve the repeatability and reproducibility of the system to some extent, and, combined with controlling the electrolyte volume, allow the system to reach a stable state in a shorter time, many problems still exist.
[0003] First, it is difficult to achieve perfect alignment between the electrode plates, resulting in poor consistency of the effective electrochemical active area. Second, the short spacing between the electrode plates makes it easy for dendrites to form during constant voltage polarization, leading to short circuits. In addition, the presence of the diaphragm introduces a new interface, which affects the AC impedance test results. Furthermore, a low electrolyte volume may cause the anions to be completely consumed in a short time, resulting in a large discrepancy between the test results and actual use. Therefore, there is an urgent need for an electrochemical test mold that can improve the accuracy and consistency of electrochemical testing, reduce external interference and errors, and obtain electrochemical test results consistent with actual use. Summary of the Invention
[0004] To address the problems existing in the prior art, this utility model provides an electrochemical testing mold that effectively solves the problems of easy short circuits between the positive and negative electrodes of traditional ion mobility number testing devices, the impact of additional diaphragms on testing accuracy, easy depletion of electrolyte, and poor consistency of testing conditions. It effectively improves the accuracy and success rate of electrochemical testing and avoids the problem of data inconsistency being affected by operation, thereby affecting the accuracy of testing.
[0005] This utility model discloses an electrochemical testing mold, including an electrolyte chamber and baffles. The electrolyte chamber includes a body with a length greater than or equal to 10 mm. The baffles are disposed at both ends of the electrolyte chamber and are used to fix the electrode plates.
[0006] The chamber has electrode-electrolyte contact holes at both ends, and the electrode sheet is connected to the electrode-electrolyte contact hole, forming a sealed environment with the chamber.
[0007] The electrolyte chamber has a first fixing plate at each end, which is fixedly connected to the chamber body. It is preferred that the two are set together. The electrode-electrolyte contact hole is set on the first fixing plate and communicates with the hollow part of the chamber body. The baffle is detachably fixed on the first fixing plate and seals the electrode sheet between the baffle and the first fixing plate.
[0008] The electrode-electrolyte contact holes on the first fixing plates at both ends of the electrolyte tank are perpendicularly aligned.
[0009] As some preferred options, the ratio of the areas of the electrode-electrolyte contact holes on the first fixing plates at both ends of the electrolyte tank is (0.8-1.3):1.
[0010] As some preferred options, the ratio of the areas of the electrode-electrolyte contact holes on the first fixing plates at both ends of the electrolyte tank is (1.01-1.3):1.
[0011] The baffle for fixing the electrode sheet is provided with at least two second fixing holes. The first fixing plate is provided with a first fixing hole that is coaxial with the second fixing holes and cooperates with them. The detachable connecting assembly passes through the first fixing hole and the second fixing hole to detachably combine the baffle with the electrolyte tank, thereby realizing the detachable fixing of the electrode sheet at both ends of the electrolyte tank.
[0012] As a further embodiment, the detachable connection assembly includes a fastening washer and a fastening assembly, with the fastening washer located at the planar interface between the fastening assembly and the baffle or the first fixing plate.
[0013] As a further option, the fastening component can be selected from either a screw-on component or a snap-on component.
[0014] As some preferred embodiments, the screw assembly includes a bolt that mates with a first fixing hole and a second fixing hole, and a nut that mates with the bolt. The bolt first passes through a fastening washer, and then passes through the first fixing hole and the second fixing hole. The nut is fitted onto the portion of the bolt that passes through the first fixing hole and the second fixing hole. A fastening washer is also fitted between the nut and the first fixing hole and the second fixing hole.
[0015] As some preferred options, the length of the electrolyte tank is selected from 10mm-60mm.
[0016] As some preferred embodiments, the length of the electrolyte tank is selected from 10mm-50mm;
[0017] As some preferred embodiments, the ratio of the cross-sectional area of the smaller end of the electrolyte tank to the length of the electrolyte tank is (2-20):(1-10).
[0018] As some preferred embodiments, the ratio of the cross-sectional area of the smaller end of the electrolyte tank to the length of the electrolyte tank is (4-10):(2-7).
[0019] As some preferred embodiments, the electrolyte tank volume is greater than 5 mL.
[0020] As some preferred embodiments, the electrode sheet includes a tab for connecting to an external circuit, a current collector, and an electrode material layer, with the electrode material layer at least disposed on the side of the current collector facing the electrolyte chamber.
[0021] As a further solution, a sealing gasket is also provided between the electrode sheet and the first fixing plate.
[0022] As some preferred embodiments, the electrode material layer on the electrode sheet is matched with the size of the electrode-electrolyte contact hole.
[0023] As some preferred embodiments, the sealing gasket is fitted with the electrode material layer.
[0024] As some preferred options, the electrolyte chamber is selected from any one of a cylinder or an N-prism.
[0025] As some preferred embodiments, N in the N-prism is selected from 3 to 15.
[0026] As some preferred embodiments, the electrode-electrolyte contact hole is selected from any one of the following: circular, elliptical, square, rectangular, triangular, or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides.
[0027] As some preferred options, the first fixing plate can be selected from any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides, and the shape and size of the baffle are consistent with those of the first fixing plate.
[0028] As some preferred options, the current collector is selected from one or more foil materials selected from copper, aluminum, nickel, tin, and stainless steel.
[0029] As some preferred embodiments, the current collector can be any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides.
[0030] As some preferred embodiments, the electrode material layer is selected from any one of lithium or sodium metal foils.
[0031] As some preferred options, the electrolyte tank, baffle, and fastening components can be made of plastic or ceramic materials.
[0032] As some preferred options, the plastic material is selected from any one of polyvinyl chloride, polyethylene, polypropylene, polystyrene, polytetrafluoroethylene, and polyetheretherketone.
[0033] As some preferred options, the ceramic material is selected from any one of alumina, zirconium oxide, silicon carbide, silicon nitride, aluminum zirconium oxide, and boron carbide.
[0034] As some preferred options, the sealing gasket material is selected from either rubber or plastic materials.
[0035] As some preferred options, the rubber material is selected from any one of nitrile rubber, fluororubber, silicone rubber, ethylene propylene rubber, chloroprene rubber, and natural rubber.
[0036] As some preferred options, the plastic material is selected from any one of polytetrafluoroethylene, polyurethane, polyethylene, and polypropylene.
[0037] As some preferred options, the material of the fastening washer is selected from either rubber or plastic.
[0038] As some preferred options, the rubber material is selected from any one of nitrile rubber, fluororubber, silicone rubber, ethylene propylene rubber, chloroprene rubber, and natural rubber.
[0039] As some preferred options, the plastic material is selected from any one of polytetrafluoroethylene, polyurethane, polyethylene, and polypropylene.
[0040] As a further option, the electrochemical testing mold proposed in this solution is not limited to any particular test object. Technicians can choose primary or secondary batteries such as lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries according to their needs.
[0041] As a further option, the electrochemical testing mold proposed in this solution is not limited to specific tests. Technicians can perform electrochemical performance tests such as impedance testing, charge-discharge testing, cycle testing, and rate testing as needed.
[0042] Compared with the prior art, the present invention has at least the following beneficial effects:
[0043] (1) In the electrochemical test mold, by increasing the electrode spacing, not only is the problem of dendrite short circuit in traditional test devices solved, the success rate and safety of the electrochemical test mold improved, but also the chamber with a diameter greater than 10 mm can effectively avoid direct contact between the electrodes, thereby avoiding the problem of increased resistance caused by the introduction of an additional diaphragm, and improving the accuracy and precision of the test.
[0044] (2) The electrolyte chamber with a volume greater than 5 mL provides an ample supply of electrolyte for electrochemical testing. This large-capacity design not only ensures sufficient electrolyte flow and balance during testing but also effectively reduces errors caused by insufficient electrolyte, thereby further improving the accuracy of the test. This optimized design is of great significance to the reliability and repeatability of experimental results, and can provide researchers with more accurate and consistent data support.
[0045] (3) The electrode-electrolyte contact holes are perpendicularly aligned, and the ratio of their two ends' areas is (0.8-1.3):1. The electrode-electrolyte contact holes ensure efficient utilization of the activation area and improve the accuracy of the test. In addition, the presence of fixed electrode-electrolyte contact holes can effectively ensure the consistency of the effective electrochemical activation range during the test, thereby further improving the accuracy of the test data and avoiding experimental errors. Attached Figure Description
[0046] The accompanying drawings, which form part of this utility model, are used to provide a further understanding of the utility model. The illustrative embodiments of the utility model and their descriptions are used to explain the utility model and do not constitute an undue limitation of the utility model. In the drawings:
[0047] Figure 1 This is a longitudinal cross-sectional view of the electrochemical testing mold;
[0048] Figure 2 An exploded view of the electrochemical testing mold;
[0049] Figure 3 Current-time plot of sample 8 in Example 1;
[0050] Figure 4 Example 1: Interface resistance change of sample 8 before and after constant voltage polarization;
[0051] Figure 5 Current-time plot of Comparative Example 1, Sample 8';
[0052] Figure 6 The graph shows the change in interfacial resistance before and after constant voltage polarization of sample 8' in Comparative Example 1.
[0053] Among them, 1-electrolyte chamber; 11-electrode-electrolyte contact hole; 12-first fixing plate; 13-chamber body; 121-first fixing hole; 2-baffle; 21-second fixing hole; 3-detachable connection assembly; 31-fastening washer; 32-fastening assembly; 321-bolt; 322-nut; 4-electrode sheet; 41-electrode tab; 42-current collector; 43-electrode material layer; 5-sealing gasket. Detailed Implementation
[0054] To facilitate understanding of this utility model, a more comprehensive description of this utility model will be given below in conjunction with the accompanying drawings, and embodiments of this utility model will be provided, but this does not limit the scope of this utility model.
[0055] This utility model discloses an electrochemical testing mold, such as Figure 1-2 The device includes an electrolyte chamber 1 and a baffle 2. The electrolyte chamber 1 includes a body 13 with a length greater than or equal to 10 mm. The baffle 2 is disposed at both ends of the electrolyte chamber 1 and is used to fix the electrode sheet 4. The body 13 has electrode-electrolyte contact holes 11 at both ends. The electrode sheet 4 is connected to the electrode-electrolyte contact holes 11, and the electrode sheet 4 and the body 13 form a sealed environment. Compared to traditional electrochemical testing devices with short distances between positive and negative electrodes and the presence of a diaphragm between them, the electrolyte chamber 1 in this invention has a length of more than 10 mm. This not only effectively avoids the problem of short circuits caused by dendrite formation due to short electrode distance, leading to test failure, but also eliminates the need for an additional diaphragm component in the electrochemical testing mold. This avoids the impact on the AC impedance testing structure caused by the introduction of a diaphragm in traditional testing devices, thus improving the testing accuracy of the electrochemical testing mold. Secondly, the presence of the electrode-electrolyte contact hole 11 ensures sufficient wetting of the electrode sheet 4 by the electrolyte, establishing a positive and negative electrode connection path. At the same time, the electrode material layer 43, which is at least partially in contact with the chamber 13 in the electrolyte chamber 1, ensures circuit continuity and, together with the chamber 13 of the electrolyte chamber 1, creates a vacuum-sealed environment, providing the necessary conditions for the construction of the electrolytic cell.
[0056] The electrolyte chamber 1 has a first fixing plate 12 at each end. The first fixing plate 12 is fixedly connected to the chamber body 13, and it is preferred that the two are set together. The electrode-electrolyte contact hole 11 is set on the first fixing plate 12 and communicates with the hollow part of the chamber body 13. The baffle 2 is detachably fixed on the first fixing plate 12 and seals the electrode sheet 4 between the baffle 2 and the first fixing plate 12. The presence of the first fixing plate 12 is conducive to maintaining a stable electrode distance.
[0057] The electrode-electrolyte contact holes 11, which are respectively set on the first fixing plates 12 at both ends of the electrolyte tank 1, are vertically aligned. The vertically aligned electrode-electrolyte contact holes 11 ensure the correspondence of the effective areas between the electrode material layers 43. This not only improves the effective electrochemical active area range, but also ensures the consistency of the effective electrochemical activation range under different tests, avoiding errors caused by the inconsistency of the effective electrochemical activation range.
[0058] As some preferred solutions, the ratio of the areas of the electrode-electrolyte contact holes 11 on the first fixing plates 12 at both ends of the electrolyte tank 1 is (0.8-1.3):1. The existence of the ratio of the areas of the electrode-electrolyte contact holes 11 ensures the efficient utilization of the activation area and improves the accuracy of the test.
[0059] As some preferred options, the ratio of the areas of the electrode-electrolyte contact holes 11 on the first fixing plates 12 at both ends of the electrolyte tank 1 is (1.01-1.3):1.
[0060] The baffle 2 for fixing the electrode sheet is provided with at least two second fixing holes 21. Figure 2 (There are four in the middle). The first fixing plate 12 is provided with a first fixing hole 121 that is coaxial with and cooperates with the second fixing hole 21. The detachable connecting component 3 passes through the first fixing hole 121 and the second fixing hole 21 to detachably combine the baffle 2 and the electrolyte tank 1, thereby realizing the detachable fixing of the electrode sheet 4 at both ends of the electrolyte tank 1.
[0061] As a further embodiment, the detachable connection assembly 3 includes a fastening washer 31 and a fastening assembly 32. The fastening washer 31 is located at the plane interface between the fastening assembly 32 and the baffle 2 or the first fixing plate 12, which is used to enhance the fastening effect of the fastening assembly 32 and also contribute to the airtightness of the electrochemical test mold.
[0062] As a further option, the fastening component 32 can be selected from either a screw-in component or a snap-fit component. The screw-in component refers to a component that fixes two or more parts together by means of a threaded connection. These components achieve a fastening connection of the parts through the biting force and clamping force of the threads. The snap-fit component refers to a component or device that is connected and fixed together by means of snapping or snapping.
[0063] As some preferred embodiments, the screw assembly includes a bolt 321 that mates with the first fixing hole 121 and the second fixing hole 21, and a nut 322 that mates with the bolt. The bolt 321 first passes through a fastening washer 31, and then passes through the first fixing hole 121 and the second fixing hole 21. The nut 322 is fitted onto the portion of the bolt 321 that passes through the first fixing hole 121 and the second fixing hole 21. A fastening washer 31 is also fitted between the nut 322 and the first fixing hole 121 and the second fixing hole 21, thereby further improving the tightness of the connection.
[0064] As some preferred embodiments, the length of the electrolyte chamber 1 is selected from 10mm-60mm. This utility model ensures that the length of the electrolyte chamber 1 is greater than 10mm-60mm. A chamber length less than 60mm can also effectively avoid the increase in resistance, thereby avoiding the impact on the electrochemical test results. In addition, the length of the electrolyte chamber 1 is greater than 10mm.
[0065] As some preferred options, the length of the electrolyte chamber 1 is selected from 10mm-50mm. The chamber length of 10mm-50mm can prevent short circuits caused by contact of the electrode plates 4. On the other hand, it can also provide a suitable ion migration distance to improve test accuracy. In addition, the chamber length of 10mm-50mm can also help to obtain a suitable constant voltage polarization time and improve test efficiency.
[0066] As some preferred solutions, the ratio of the cross-sectional area of the smaller end of the electrolyte chamber (1) to the length of the electrolyte chamber (1) is (2-20):(1-10). The setting of the ratio of the cross-sectional area of the smaller end of the electrolyte chamber (1) to the length of the electrolyte chamber (1) ensures that the electrode sheet 4 is fully wetted, while ensuring that there is a sufficient amount of electrolyte in the electrolyte chamber to ensure ion transport, thereby improving the stability and success rate of the test.
[0067] As some preferred options, the ratio of the cross-sectional area of the smaller end of the electrolyte tank (1) to the length of the electrolyte tank (1) is (4-10):(2-7), which helps to further improve the success rate and stability of the test.
[0068] As some preferred embodiments, the electrolyte chamber 1 has a volume greater than 5 mL. A volume greater than 5 mL helps to avoid the amplification of capillary action of the electrode active material due to the small volume of the electrolyte chamber 1, which could lead to the drying up of the electrolyte inside the chamber and improve the accuracy of the test.
[0069] As a further embodiment, the electrode sheet 4 includes a tab 41 for connecting to an external circuit, a current collector 42, and an electrode material layer 43. The electrode material layer 43 is at least disposed on the side of the current collector 42 facing the electrolyte chamber 1. Integrating the tab 41 onto the electrode sheet 4 strengthens the connection between the tab 41 and the electrode, avoiding the impact on electrochemical test results due to poor contact between the tab 41 and the electrode. At the same time, the design of the electrode sheet 4 can also effectively reduce the internal connection resistance of the battery, further improving the accuracy of electrochemical testing.
[0070] As a further solution, a sealing gasket 5 is provided between the electrode sheet 4 and the first fixing plate 12; the presence of the sealing gasket 5 prevents external air from seeping into the electrolytic cell to the greatest extent, thus ensuring the vacuum environment of the electrolytic cell.
[0071] As some preferred embodiments, the electrode material layer 43 on the electrode sheet 4 is matched with the size of the electrode-electrolyte contact hole 11, which helps to further ensure that the electrolyte fully wets the electrode sheet and improves the airtightness of the electrolyte chamber, reducing error problems caused by insufficient contact between the electrolyte and the electrode sheet or insufficient airtightness of the electrolytic cell environment.
[0072] As some preferred embodiments, the sealing gasket 5 cooperates with the electrode material layer 43 to limit the electrode material layer 43. The presence of the sealing gasket 5 cooperating with the electrode material layer 43 further improves the airtightness of the electrochemical test mold and improves the accuracy of the test.
[0073] As some preferred options, the electrolyte tank 1 is selected from any one of a cylinder or an N-prism.
[0074] As some preferred embodiments, N in the N-prism is selected from 3 to 15.
[0075] As some preferred embodiments, the electrode-electrolyte contact hole 11 is selected from any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides.
[0076] As some preferred options, the first fixing plate 12 can be selected from any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides, and the shape and size of the baffle 2 are consistent with those of the first fixing plate 12.
[0077] As some preferred embodiments, the current collector 42 is selected from one or more foil materials selected from copper, aluminum, nickel, tin, and stainless steel.
[0078] As some preferred options, the current collector 42 can be any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides.
[0079] As some preferred options, the electrode material layer 43 is selected from any one of lithium or sodium metal foils.
[0080] As some preferred options, the electrolyte tank 1, baffle 2, and fastening assembly 32 can be made of plastic or ceramic materials.
[0081] As some preferred options, the plastic material is selected from any one of polyvinyl chloride, polyethylene, polypropylene, polystyrene, polytetrafluoroethylene, and polyetheretherketone.
[0082] As some preferred options, the ceramic material is selected from any one of alumina, zirconium oxide, silicon carbide, silicon nitride, aluminum zirconium oxide, and boron carbide.
[0083] As some preferred options, the sealing gasket 5 is made of either rubber or plastic.
[0084] As some preferred options, the rubber material is selected from any one of nitrile rubber, fluororubber, silicone rubber, ethylene propylene rubber, chloroprene rubber, and natural rubber.
[0085] As some preferred options, the plastic material is selected from any one of polytetrafluoroethylene, polyurethane, polyethylene, and polypropylene.
[0086] As some preferred options, the material of the fastening washer 31 is selected from either rubber or plastic.
[0087] As some preferred options, the rubber material is selected from any one of nitrile rubber, fluororubber, silicone rubber, ethylene propylene rubber, chloroprene rubber, and natural rubber.
[0088] As some preferred options, the plastic material is selected from any one of polytetrafluoroethylene, polyurethane, polyethylene, and polypropylene.
[0089] As a further option, the electrochemical testing mold proposed in this solution is not limited to any particular test object. Technicians can choose primary or secondary batteries such as lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries according to their needs.
[0090] As a further option, the electrochemical testing mold proposed in this solution is not limited to specific tests. Technicians can perform electrochemical performance tests such as impedance testing, charge-discharge testing, cycle testing, and rate testing as needed.
[0091] When the electrochemical testing mold is used for testing, firstly, in the glove box, place the sealing gasket 5 on the electrode-electrolyte contact hole 11 at one end of the electrolyte tank 1, then place the electrode sheet 4 on the sealing gasket 5, and ensure that the electrode material layer 43 is at least partially exposed to the tank body 13 of the electrolyte tank 1. Align the second fixing hole 21 on the baffle 2 with the first fixing hole 121 on the first fixing plate 12 on which the electrode sheet 4 has been loaded, and fix the baffle 2 on the first fixing plate 12 using bolts 321 and nuts 322.
[0092] Subsequently, the substance to be tested is injected through the electrode-electrolyte contact hole 11 at the idle end of the first fixed plate 12, and the sealing gasket 5, electrode sheet 4, and baffle 2 are sequentially stacked on the first fixed plate 12 at the end where the substance to be tested is injected. The electrode material layer 43 on the electrode sheet 4 is snapped into the sealing gasket 5 and the electrode-electrolyte contact hole 11, and the second fixing hole 21 on the baffle 2 is aligned with the first fixing hole 121 on the first fixed plate 12 at this end. The baffle 2 is fixed on the first fixed plate 12 by bolts 321 and nuts 322. After standing for a certain period of time, the electrochemical workstation is connected through the tab 41, and the test can be performed. After the test is completed, the connection between the tab 41 and the electrochemical workstation is disconnected, the mold is disassembled, and one test is completed.
[0093] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0094] Example 1
[0095] Lithium-ion transference number test using the electrochemical test mold proposed in this invention.
[0096] The chamber 13 is 50mm long, with copper foil as the current collector 42 and lithium foil as the electrode material layer 43, and the lithium-ion battery electrolyte LBC3045i is tested.
[0097] When the electrochemical testing mold is used for testing, firstly, in the glove box, place the sealing gasket 5 on the electrode-electrolyte contact hole 11 at one end of the electrolyte tank 1, then place the electrode sheet 4 on the sealing gasket 5, ensuring that at least part of the electrode material layer 43 is exposed to the hollow part of the electrolyte tank 1 body 13. Align the second fixing hole 21 on the baffle 2 with the first fixing hole 121 on the first fixing plate 12 on which the electrode sheet 4 has been loaded, and use bolts 321 and nuts 322 to fix the baffle 2 on the first fixing plate 12.
[0098] Subsequently, lithium-ion battery electrolyte LBC3045i is injected through the electrode-electrolyte contact hole 11 at the idle end of the first fixed plate 12. The sealing gasket 5, electrode sheet 4, and baffle 2 are sequentially stacked on the first fixed plate 12 at the end where the test substance is injected. The electrode material layer 43 on the electrode sheet 4 is snapped into the sealing gasket 5 and the electrode-electrolyte contact hole 11, and the second fixing hole 21 on the baffle 2 is aligned with the first fixing hole 121 on the first fixed plate 12 at this end. The baffle 2 is fixed on the first fixed plate 12 by bolts 321 and nuts 322. After standing for 4 hours, the electrochemical workstation is connected through the tab 41 to perform AC impedance testing and constant voltage polarization testing. After the constant voltage polarization test, a second AC impedance test is performed. After the test is completed, the connection between the tab 41 and the electrochemical workstation is disconnected, the mold is disassembled, and the test is completed in one go. The same electrode sheet 4 and the same lithium-ion battery electrolyte LBC3045i were repeatedly assembled and tested 8 times, which were recorded as sample 1 to sample 8. The test results are shown in Table 1.
[0099] Comparative Example 1
[0100] Electrode sheets were prepared using copper foil as the current collector and lithium foil as the electrode. Lithium-ion battery electrolyte LBC3045i was used as the electrolyte, and Celgard 2325 was used as the separator. Button batteries were assembled in a glove box, sealed, and left to stand for 4 hours. Then, AC impedance testing and constant voltage polarization testing were performed. After the constant voltage polarization test, a second AC impedance test was performed. The test results are recorded as Sample 1'-Sample 8'. The test results are shown in Table 1.
[0101] Data processing
[0102] The interface impedance before and after constant voltage polarization test is obtained by fitting the equivalent circuit. The current at the initial and equilibrium of constant voltage polarization is read, and the lithium-ion transference number is calculated by formula (1).
[0103]
[0104] Among them, t + I0 is the lithium-ion transference number, I0 is the initial polarization current, and I0 is the initial polarization current. S R is the equilibrium current, R0 is the initial polarization interface impedance, and R S When balanced, the interface resistance ΔV is the magnitude of the bias voltage.
[0105] When the lithium-ion transference number is ≥1, a side reaction is considered to have occurred; when the transference number is <0.1, the reaction is considered to be short-circuited. Therefore, samples with a lithium-ion transference number ≥1 or <0.1 are considered invalid samples, and the measured lithium-ion transference number is invalid data and is not included in the calculation of the average lithium-ion transference number.
[0106] Furthermore, based on the interface resistance change diagram before and after constant voltage polarization, samples with short circuits are considered invalid data and are not included in the calculation of the average lithium-ion transference number.
[0107] Average lithium-ion transport number = (sum of lithium-ion transport numbers of effective samples) / number of effective samples * 100%;
[0108] According to the literature, the lithium-ion transference number of the lithium-ion battery electrolyte LBC3045i is 0.43.
[0109] Table 1
[0110]
[0111] Note: According to Figure 6 It can be seen that sample 8' of Comparative Example 1 has a short circuit, therefore sample 8' is considered invalid data.
[0112] By comparing samples 1-8 in Example 1 with samples 1'-8' in Comparative Example 1, it can be observed that samples 1-8 in Example 1 exhibit a higher test success rate and a more accurate average lithium-ion migration number compared to ordinary button batteries.
[0113] From the test success rate of Example 1 and Comparative Example 1, it can be observed that the electrolyte tank 1 with a length greater than 10 mm can effectively improve the short circuit between the positive and negative electrodes. Furthermore, Figure 3 , Figure 5 This also confirms the role of the electrolyte chamber 1 with a length greater than 10 mm. Therefore, compared with the traditional lithium-ion migration test device, the electrochemical test mold proposed in this utility model has higher safety and test efficiency.
[0114] Furthermore, based on the average lithium-ion migration counts of Example 1 and Comparative Example 1, it can be observed that the average lithium-ion migration count of Example 1 is significantly close to the standard lithium-ion migration count of the lithium-ion battery electrolyte LBC3045i, while the equilibrium lithium-ion migration count obtained by the button cell test has an error of 0.34. This may be because, compared to traditional button cells, the electrochemical testing mold proposed in this invention, due to its greater distance between the positive and negative electrodes, does not require the introduction of an additional separator, thus avoiding errors caused by the introduction of a separator. In addition, in this invention, the electrode-electrolyte contact holes 11, which are perpendicularly aligned and have an area ratio of (0.8-1.3):1, ensure that the effective electrochemical activation range between the positive and negative electrodes is completely corresponding, ensuring the consistency of experimental data and further improving the accuracy of test data. Therefore, the accuracy of the average lithium-ion migration count of Example 1 is much higher than that of the average lithium-ion migration count obtained by the Comparative Example 1 test.
[0115] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of the different embodiments or examples.
Claims
1. An electrochemical testing mold, characterized in that, It includes an electrolyte tank (1) and a baffle (2). The electrolyte tank (1) includes a chamber (13) with a length greater than or equal to 10 mm. The baffle (2) is disposed at both ends of the electrolyte tank (1) and is used to fix the electrode sheet (4). The chamber (13) has electrode-electrolyte contact holes (11) at both ends. The electrode sheet (4) is connected to the electrode-electrolyte contact hole (11). The electrode sheet (4) and the chamber (13) form a sealed environment.
2. The electrochemical testing mold according to claim 1, characterized in that, The electrolyte chamber (1) is provided with a first fixing plate (12) at both ends. The first fixing plate (12) is fixedly connected to the chamber body (13). The electrode-electrolyte contact hole (11) is placed on the first fixing plate (12) and communicates with the hollow part of the chamber body (13). The baffle (2) is detachably fixed on the first fixing plate (12) and seals the electrode sheet (4) between the baffle (2) and the first fixing plate (12). The electrode-electrolyte contact holes (11) provided on the first fixing plates (12) at both ends of the electrolyte chamber (1) are perpendicular to each other, and the ratio of the areas of the two ends is (0.8-1.3):
1.
3. The electrochemical testing mold according to claim 2, characterized in that, The baffle (2) is provided with at least two second fixing holes (21), and the first fixing plate (12) is provided with a first fixing hole (121) that is coaxial with the second fixing holes (21) and cooperates with each other. The detachable connecting assembly (3) passes through the first fixing hole (121) and the second fixing hole (21) to detachably combine the baffle (2) with the electrolyte tank (1).
4. The electrochemical testing mold according to claim 1, characterized in that, The electrochemical test mold also includes a detachable connection component (3), which includes a fastening washer (31) and a fastening component (32). The fastening washer (31) is located at the plane interface between the fastening component (32) and the baffle (2) or the first fixing plate (12).
5. The electrochemical testing mold according to claim 1, characterized in that, The length of the electrolyte tank (1) body (13) is selected from 10mm-60mm.
6. The electrochemical testing mold according to claim 1, characterized in that, The electrode sheet (4) includes a tab (41) for connecting to an external circuit, a current collector (42), and an electrode material layer (43), with the electrode material layer (43) being disposed at least on the side of the current collector (42) facing the electrolyte chamber (1).
7. The electrochemical testing mold according to claim 1, characterized in that, The electrolyte chamber (1) is selected from any one of cylinders or N-prisms.
8. The electrochemical testing mold according to claim 1, characterized in that, The electrolyte tank (1), baffle (2), and fastening assembly (32) can be made of either plastic or ceramic.
9. An electrochemical testing mold according to claim 4, characterized in that, The fastening component (32) is made of either plastic or ceramic.
10. An electrochemical testing mold according to claim 6, characterized in that, The current collector (42) is selected from one or more foil materials selected from copper, aluminum, nickel, tin and stainless steel.
11. The electrochemical testing mold according to claim 2, characterized in that, The ratio of the area of the electrode-electrolyte contact hole (11) set on the first fixing plate (12) at both ends of the electrolyte tank (1) is (1.01-1.3):
1.
12. The electrochemical testing mold according to claim 4, characterized in that, The fastening component (32) can be selected from either the screw component or the snap-fit component.
13. The electrochemical testing mold according to claim 12, characterized in that, The screw assembly includes a bolt (321) that mates with a first fixing hole (121) and a second fixing hole (21) and a nut (322) that mates with the bolt. The bolt (321) first passes through a fastening washer (31), and then passes through the first fixing hole (121) and the second fixing hole (21). The nut (322) is fitted onto the portion of the bolt (321) that passes through the first fixing hole (121) and the second fixing hole (21). A fastening washer (31) is also fitted between the nut (322) and the first fixing hole (121) and the second fixing hole (21).
14. The electrochemical testing mold according to claim 1, characterized in that, The length of the electrolyte tank (1) body (13) is selected from 10mm-50mm.
15. The electrochemical testing mold according to claim 1, characterized in that, The ratio of the cross-sectional area of the smaller end of the electrolyte tank (1) to the length of the electrolyte tank (1) is (2-20):(1-10).
16. The electrochemical testing mold according to claim 1, characterized in that, The ratio of the cross-sectional area of the smaller end of the electrolyte tank (1) to the length of the electrolyte tank (1) is (4-10):(2-7).
17. The electrochemical testing mold according to claim 1, characterized in that, The electrolyte chamber (1) has a volume greater than 5 mL.
18. The electrochemical testing mold according to claim 1, characterized in that, A sealing gasket (5) is also provided between the electrode sheet (4) and the first fixing plate (12).
19. The electrochemical testing mold according to claim 1, characterized in that, The electrode material layer (43) on the electrode sheet (4) is matched with the size of the electrode-electrolyte contact hole (11).
20. The electrochemical testing mold according to claim 18, characterized in that, The sealing gasket (5) is fitted with the electrode material layer (43).
21. The electrochemical testing mold according to claim 7, characterized in that, In the N-prism, N is selected from 3 to 15.
22. The electrochemical testing mold according to claim 1, characterized in that, The electrode-electrolyte contact hole (11) is selected from any one of the following: circle, ellipse, square, rectangle, triangle or regular polygon, and the regular polygon refers to a regular polygon with fewer than 10 sides.
23. The electrochemical testing mold according to claim 2, characterized in that, The first fixing plate (12) can be selected from any one of the following: circle, ellipse, square, rectangle, triangle or regular polygon. The regular polygon refers to a regular polygon with fewer than 10 sides. The shape of the baffle (2) is consistent with the size of the first fixing plate (12).
24. The electrochemical testing mold according to claim 6, characterized in that, The current collector (42) can be any one of a circle, ellipse, square, rectangle, triangle or regular polygon, wherein the regular polygon refers to a regular polygon with fewer than 10 sides.
25. The electrochemical testing mold according to claim 4, characterized in that, The material of the fastening washer (31) is selected from rubber or plastic.
26. The electrochemical testing mold according to claim 6, characterized in that, The electrode material layer (43) is any metal foil of lithium or sodium.
27. The electrochemical testing mold according to claim 18, characterized in that, The sealing gasket (5) is made of either rubber or plastic.
Citation Information
Patent Citations
Lithium ion battery electrolyte lithium ion migration number testing device
CN210514170U